1992
DOI: 10.1162/pres.1992.1.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Cybersickness: Perception of Self-Motion in Virtual Environments

Abstract: Human perceptual systems have evolved to provide accurate information about orientation and movement through the environment. However, these systems have been challenged in the past century by modern transportation devices and will be further challenged by virtual environments (VEs) and teleoperator systems. Illusory self-motion within a VE (“cyberspace”) will be entertaining and instructive, but for many users it will result in motion sickness (“cybersickness”). Sensory conflict theory and the poison hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
245
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 410 publications
(248 citation statements)
references
References 4 publications
1
245
0
2
Order By: Relevance
“…The motion sickness experienced with HMDs is most appropriately referred to as 'cybersickness' [11,23]. In principle, the cybersickness experienced while wearing an HMD could be visual, nonvisual or even multisensory in origin [4,22].…”
Section: Introductionmentioning
confidence: 99%
“…The motion sickness experienced with HMDs is most appropriately referred to as 'cybersickness' [11,23]. In principle, the cybersickness experienced while wearing an HMD could be visual, nonvisual or even multisensory in origin [4,22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kennedy,Fowlkes,and Lilienthal [13], have shown that following exposure to virtual environments and simulators, up to 30% of exposures result in reported nausea, up to 40% of exposures result in reported eyestrain, as well as the experience of numerous other symptoms of motion sickness including drowsiness, salivation, sweating, headache, and dizziness/vertigo, and loss of postural stability. Although the prevalence of motion sickness in virtual environments appears greater than in flight simulators [14], results are generally based upon survey and selfreported measures rather than controlled experiments [15], [16].…”
Section: Motion Sickness In Virtual Environmentsmentioning
confidence: 99%
“…Another important concept to address before describing the treatment manual is the potential negative side effects that can be induced by the immersion in VR. These unwanted side effects are often called "cybersickness" [34], although they do not refer to an actual sickness or illness. The term was coined following the use of common expressions such as sea sickness, motion sickness and simulator sickness.…”
Section: Internal Factorsmentioning
confidence: 99%